Antimicrobial Microwebs of DNA–Histone Inspired from Neutrophil Extracellular Traps. Issue 14 (30th January 2019) - Song, Yang; Kadiyala, Usha; Weerappuli, Priyan; Valdez, Jordan J.; Yalavarthi, Srilakshmi; Louttit, Cameron; Knight, Jason S.; Moon, James J.; Weiss, David S.; VanEpps, J. Scott; Takayama, Shuichi
Abstract: Neutrophil extracellular traps (NETs) are decondensed chromatin networks released by neutrophils that can trap and kill pathogens but can also paradoxically promote biofilms. The mechanism of NET functions remains ambiguous, at least in part, due to their complex and variable compositions. To unravel the antimicrobial performance of NETs, a minimalistic NET‐like synthetic structure, termed "microwebs, " is produced by the sonochemical complexation of DNA and histone. The prepared microwebs have structural similarity to NETs at the nanometer to micrometer dimensions but with well‐defined molecular compositions. Microwebs prepared with different DNA to histone ratios show that microwebs trap pathogenic Escherichia coli in a manner similar to NETs when the zeta potential of the microwebs is positive. The DNA nanofiber networks and the bactericidal histone constituting the microwebs inhibit the growth of E. coli . Moreover, microwebs work synergistically with colistin sulfate, a common and a last‐resort antibiotic, by targeting the cell envelope of pathogenic bacteria. The synthesis of microwebs enables mechanistic studies not possible with NETs, and it opens new possibilities for constructing biomimetic bacterial microenvironments to better understand and predict physiological pathogen responses. Abstract : Microwebs with bacteria trapping and killing functions are designed to mimic neutrophil extracellular traps—an immune defense weapon to fight against invading pathogens. The composition–structure–function relationship of the synthetic structure is discussed, and the collaborative action between microwebs and antibiotics allows better elimination of pathogenic bacteria, Escherichia coli .